Cyberpolitics and Digital Democracy: The Role of Instagram in the 2024 Makassar City Election Campaign - Noviano Patty, Alberto; Qolbi, Yahdi; Dyastari, Letizia; Mujiburrahman, M.; Asbudi, A. (Manunggal Halim Jaya, 2025)
This research discusses the phenomenon of cyberpolitics as a digital democratic space with a focus on political campaigns through Instagram in the 2024 Makassar Pilwalkot. Social media, especially Instagram, is used intensely by candidate pairs to build a political image and convey work programs visually to the public. On the other hand, millennials, as the dominant social media users, utilise the platform to access political information, interact directly with candidates, and determine voting preferences. Through a literature study approach and content analysis, this research shows that digital space has great potential in expanding horizontal political participation. However, the effectiveness of cyberspace as a democratic arena cannot be separated from challenges such as symbolic participation, algorithm dominance, and digital literacy gaps. Instagram has been proven to facilitate the political participation of the younger generation. However, it has not been able to fully bridge the inequality of political representation due to digital exclusion. By applying the theories of agenda setting, political efficacy, and networked public sphere, this study concludes that the quality of political communication, information disclosure, and the critical capacity of digital citizens largely determine the success of digital democracy in cyberspace.